2012
DOI: 10.1364/ao.51.002441
|View full text |Cite
|
Sign up to set email alerts
|

Optical eye tracking system for noninvasive and automatic monitoring of eye position and movements in radiotherapy treatments of ocular tumors

Abstract: A noninvasive eye tracking system based on infrared 3-D video-oculographic techniques is proposed for the automatic monitoring of eye position and orientation in external beam radiotherapy of ocular tumors. The presented method can be applied for the real-time estimation of lesion position and tumor-beam misalignments, allowing automatic patient setup and eye movement gated treatments. A prototypal eye tracker was developed and tested on five subjects, achieving gaze estimation errors of 0.5° and eye monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The eye tracker is based on non-invasive 3D video-oculography (VOG) techniques, by detecting ocular features on the video images captured by a pair of calibrated cameras [49]. The recognition of pupil contour and corneal reflections produced by two nearinfrared (NIR) light sources allows the estimation of pupil and cornea centers in 3D, which are used to reconstruct an eyeball local coordinate system.…”
Section: Ocular Treatments: a Novel Approachmentioning
confidence: 99%
“…The eye tracker is based on non-invasive 3D video-oculography (VOG) techniques, by detecting ocular features on the video images captured by a pair of calibrated cameras [49]. The recognition of pupil contour and corneal reflections produced by two nearinfrared (NIR) light sources allows the estimation of pupil and cornea centers in 3D, which are used to reconstruct an eyeball local coordinate system.…”
Section: Ocular Treatments: a Novel Approachmentioning
confidence: 99%
“…6). Fassi et al 14 reported an average angular accuracy of 0.5 • evaluated based on five human subjects. With an average registration error below 0.36 • for tilting even with a sparse sampling of 125 × 125 A-scans, the proposed method yields improved angular accuracy for tilting.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, different approaches have been applied including suction devices, 9 retro-or parabulbar anaesthesia, 10 or active fixation of light points. [11][12][13][14] Suction devices are very uncomfortable and may cause damage to the anterior eye segment. Local anaesthesia is associated with discomfort for the patient and induces displacement of the eyeball in the orbit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ETS is based on noninvasive 3D video-oculography (VOG) and is capable of detecting ocular features on the video image stream coming from a pair of calibrated cameras. 18,19 The system stems from a first prototype described by Fassi et al; 20 it features a new design compatible with clinical usability and incorporates specific algorithms for the automatic detection of torsional eye movements, which were found to be relevant in laser refractive surgery. Liu et al, 21 and Kim and Joo 22 reported median eye cyclotorsion of 3 • between seated and supine positions with values higher than 5 • on 20% of the investigated cases.…”
Section: Introductionmentioning
confidence: 99%